From Dunes to Shelf Deposits: A Multidisciplinary Investigation of Coastal Sand Management in North Carolina - Conery, Ian W. (East Carolina University, 2019)
Coastlines around the world are environmentally and economically crucial to society but are being threatened by storms, sea-level rise and erosion. Beach nourishment is a widely used shoreline stabilization strategy that creates increased storm protection and other physical and economic benefits. This dissertation investigated multiple geologic and economic questions related to the management of sandy coastlines in North Carolina (NC), and work is separated into three chapters addressing different aspects. Using 22 months of terrestrial laser scanning, this research examined the evolution of a nourished, managed versus a non-managed beach-dune system and associated drivers of change. Largely due to anthropogenic factors (e.g., fencing and plantings) and increased sediment supply at the nourished site, the managed dunes accreted 1.7 times faster than the dunes in the unmanaged system. Observations showed storms are not just erosional, but also can increase overall dune volumes during optimal wind conditions, despite scarping to the dune toe. As erosion and sea-level rise persist, beach nourishment will continue, if not increase in the future. Because nearshore sand borrow sources may diminish, continental shelf resources may become necessary. This work examined the distribution of potential sand sources offshore southern NC. More than 300 nm (55 km) of sub-bottom, sidescan and core data showed the distribution of modern sand is complex and irregular. Some paleochannels contained viable sediment for beach nourishment, however, variable lithologies in others are not usable as a sand resource. Overall, geologic framework significantly influences the complex distribution of potential sand resources, hardbottom, and paleochannels. Reconnaissance data such as those produced for this study are critical to prevent multi-use conflicts on shelf areas under increasing demand (e.g,. wind, oil/gas). Nourishment is costly due to comprehensive geologic surveying and engineering practices. The last chapter investigated several communities in northeast NC (Dare County) that have recently used local funding to pay for expensive projects through county-derived occupancy taxes and municipal service tax districts. Oceanfront homeowners clearly receive the most benefits from nourishment, however this work examined the coastal housing market and homeowner's responses to nourishment. Results showed inland and soundfront homeowners capitalized on the opportunity to rent due to increased amenity value from nourishment. Increased rentals generate more in occupancy taxes and should be considered by policymakers when developing funding structures and assessing the long-term sustainability of nourishment. Overall, this research highlights the complexity of several integrated geologic, economic and policy issues on the coast. Coastal managers and planners should incorporate an understanding of these coupled natural and human responses to future management of sandy shorelines.
Keywords: Coastal Foredunes; Remote Sensing; Aeolian Transport; Offshore Sand Borrow Sources; Continental Shelf Geology; Geophysics; Environmental Resource Economics; Coastal zone management--North Carolina; Beach nourishment--North Carolina; Geomorphology--North Carolina; Sand dune management--North Carolina; Erosion--North Carolina